1
$\begingroup$

Say I want to find the Fourier transform of the following distribution: enter image description here

The solution I have uses the physicist's definition of the Dirac $\delta$-function $\delta(x) = \int_\mathbb{R} e^{-i x y} dy$ which is mathematically ill-defined: Physicist's solution

I cannot figure out how to solve this problem in a mathematically rigorous way, using only the allowed operations on distributions, though it should be possible to do...

Any help is appreciated.

$\endgroup$
  • $\begingroup$ First, $\langle U, \phi\rangle = \langle 1\otimes \delta\rangle$; second, you can apply FT to each part of the tensor product separately. $\endgroup$ – TZakrevskiy Jan 31 '17 at 9:13
1
$\begingroup$

First - I will apply Foubini theorem a lot of times, since test functions are very integrable=) Second - I will systematically omit all normalisation constants in Fourier transform, as well as integration limits. Third - I will denote by $\phi_y(x) = \phi(x,y)$. $\forall y\quad \phi_y\in D(\Bbb R^m)$. Fourth - the corresponding Fourier variables to $(x,y)$ will be $(\xi,\eta)$.

By definition we can write

$$\langle \hat U, \phi(x,y)\rangle = \left\langle U, \int\phi(x,y) \exp(ix\xi + i y\eta) dx\,dy\right\rangle$$ $$=\int \left(\int\phi(x,y) \exp(ix\xi + i y\eta) dx\,dy\right)\big|_{\eta=0}d\xi$$ Since everything is smooth, we can pass the value of $\eta=0$ inside the integral: $$=\int \left(\int\phi(x,y) \exp(ix\xi) dx\,dy\right) d\xi$$ $$=\int dy\int d\xi \left(\int\phi_y(x) \exp(ix\xi) dx \right) $$ $$=\int dy \left\langle 1, \hat \phi_y(\xi)\right\rangle$$ (in the last integral $\hat \phi_y(\xi)$ is a FT with respect to $x$, and $1$ is a distribution acting on the variable $\xi$) $$=\int dy \left\langle \hat 1, \phi_y(x)\right\rangle$$ $$=\int dy \left\langle \delta_0, \phi_y(x)\right\rangle$$ $$=\int \phi_y(0) dy = \int \phi(0,y)dy.$$

In other words, you initial distriubtions is, in fact, a tensor product $1\otimes \delta_0$; you apply FT to this distribution, and you will get $$F[1\otimes \delta_0] = F[1]\otimes F[\delta_0] = \delta_0\otimes 1,$$ which coreponds to out previous result.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.